Spiritual and value identification in the discourse of Russian printed media: between nationalism and cosmopolitanism: Духовно-ценностная идентификация в дискурсе российских печатных СМИ: между национализмом и космополитизмом - Antropova, Vera (Przegląd Wschodnioeuropejski, 2020)
The article reveals the specific of the spiritual and value identification in the discourse of media which is defined with the amount of presence of national and cosmopolitan components. The cosmopolitan texts are twice as many, though they carry different cognitive and semantic mechanisms of spiritual and value field model. The quality press represents both national and cosmopolitan components through a rich variety of cultural artifacts involved in existential and intellectual personal reflection. Due to this a high degree of abstraction of national and spiritual meanings is reached with the focus on the most important vital beginnings. The mass editions present national and spiritual meanings through the narrow and expected circle of traditional cultural signs, so they form the identity through copying of national historical symbols and nationally meaning ideas. The cosmopolitan component is objectified through the culture of contemporary consumption as the unifying stimulus.